Highly Efficient Li-Air Battery Using Ultra-Thin Air Electrode. Issue 15 (25th October 2019) - Li, Jie; Su, Zipeng; Zhang, Tianyu; Li, Qiang; Yu, Mingfu; Zhang, Xiaochen; Sun, Hong
Abstract : A two-dimensional, transient state model was developed by the dynamic behavior of the porous cathode, which was determined by a numerical solution of the combined continuity, transport, and kinetics equations. The effects of ultra-thin air electrode on the distribution of the oxygen concentration, Li2 O2  volume fraction, porosity, and local oxygen reduction reaction rate on the properties of non-aqueous Li-air battery during discharge were investigated. The time dependence of the battery system and the mass transport along the depth of the air electrode were considered and analyzed. The model was validated against the voltage-capacity data measured at different discharging current densities. The optimal ultra-thin thickness of the air electrode was achieved. The results revealed that employing ultra-thin air electrode leaded to the smooth oxygen diffusion, uniform porosity and Li2 O2 deposition and remarkable specific capacity of Li-air battery. The discharge current density had significant effects on the property of Li-air battery based on ultra-thin air electrode due to the great increasing of ohm polarization and serious air electrode passivation. The influence of the initial oxygen concentration on the battery performance was relatively small caused by the high oxygen saturation in the ultra-thin air electrode. The detailed results provided a deeper understanding of producing more efficient Li-air batteries as potential power sources to expand the range of electric vehicles.